The book of Clarence [videorecording (DVD)] - Samuel, Jeymes, 1979-; Samuel, Jeymes, 1979-; Stanfield, LaKeith, 1991-; Sy, Omar, 1978-; Diop, Anna, 1988-; Cyler, RJ (Ronald J), 1995-; Oyelowo, David; Ward, Micheal, 1995-; Woodard, Alfre, 1953-; Taylor, Teyana, 1990-; McLaughlin, Caleb, 2001-; Abrefa, Eric Kofi; et al. (Sony Pictures Home Entertainment, 2024)
Striving to find a better life, Clarence is enthralled by the power of the rising Messiah and soon risks everything to carve a path to a divine existence.